The Influence of the Work Environment on Employee Performance at PT. Perdana Jaya Eternal Success Palembang - Pertiwi, Krisma Gita; Handayani, Susi; Veronica, Meilin (International Journal of Marketing & Human Resource Research, 2024)
This study aims to determine the effect of the work environment on employee performance at PT. Perdana Jaya Eternal Success Palembang. The number of samples in this study were 60 employees. The data collection technique in this study was using a questionnaire. The method of analysis in this study was simple linear regression analysis. Based on the Coefficient of Determination Test, the value of the coefficient of determination is 0.591. This means that the ability of the work environment (X) to employee performance (Y) is 59.1%. The results show that the work environment affects the performance of employees at PT. Perdana Jaya Eternal Success Palembang. The results of this study are expected to be used as a company evaluation to improve employee performance through the work environment.